Pembentukan Sistem Pencatatan Akuntansi pada The Calokies - Hendi, Hendi; Kellyn, Kellyn (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was carried out to assist The Calokies, a culinary MSME that still uses a basic financial recording process through Microsoft Excel, resulting in inefficient report preparation and a higher risk of inaccuracy. The objective of this program is to design and implement a more integrated accounting recording system tailored to the business’s operational needs. The implementation methods included interviews, direct observation, system design using Microsoft Access, as well as training and evaluation with the business owner. The developed system is capable of producing financial reports more quickly and accurately, while supporting compliance with accounting principles and tax regulations. The results of the program indicate improved efficiency and accuracy in financial recording, which positively influences decision-making processes. These findings are significant because a structured accounting system helps MSMEs enhance financial management and business sustainability.